A DNA algorithm for feature selection in condition monitoring of manufacturing processes - Quan-Fang Wang; Ruxu Du (2005 International Symposium on Intelligent Signal Processing and Communications Systems, 2005)
This paper proposes a DNA based algorithm for signal processing in condition monitoring of manufacturing processes. Its goal is to find the 'DNA' (feature) of monitoring signal through DNA encoding and analysis. Furthermore, features selection is implemented for vibration signal collecting from the injection molding machine to verify the DNA algorithm.